Protease inhibitors in inflammatory synovial effusions. - Hadler, N M (1981)
Granulocyte lysosomal enzymes can potentially participate in cartilage degradation in inflammatory arthritides. However, we have shown that the quantity of several such enzymes in an inflammatory synovial effusion correlates negatively with the degree of radiographic damage of the joint from which the fluid was sampled. In the current work the quantity of the following 5 protease inhibitors was determined immunochemically in the same fluids: alpha 1 antitrypsin, alpha 1-antichymotrypsin, alpha 2-macroglobulin, inter-alpha-trypsin inhibitor, and Cl esterase inhibitor. These inhibitors are generally covariate and correlate positively with the total protein in the fluid as well as the number of granulocytes and the concentration of granulocyte lysosomal enzymes in the fluid. As did the lysosomal enzymes, the protease inhibitors correlate negatively with radiographic destruction. It is likely that lysosomal enzymes in solution in inflammatory synovial effusions are rendered effete by the presence of protease inhibitors.